Relationships of changes of atmospheric pressure and heart rate in winterers in Antarctica: mathematical modelling and analysis - Moiseyenko, E.V.; Utevsky, A.Yu.; Bondarenko, T.P.; Nosov, K.V.; Bespalov, Yu.G. (Ukrainian Antarctic Journal, 2015)
This research is aimed at estimating the power of mathematical modeling for analyzing results of the simultaneous monitoring of biomedical and meteorological indications during а long Antarctic expedition at the Antarctic station "Akademik Vernadsky". The database of atmospheric pressure and personnel physiological parameters during the Antarctic expedition (11 men aged 23 - 48 years) were used. We showed the possibility of using mathematical models (discrete models of dynamic systems) for determining the sustainability of regulatory influences of the autonomic nervous system to а change in atmospheric pressure in the Antarctic. The results of our model-mathematical analysis allows to evaluate the level of sensitivity of regulation mechanisms of cardiac rhythm to the action of changes in barometric pressure during the Antarctic wintering.